An Empirical Assessment of Artificial Intelligence-Based Deep Reinforced Learning in Automatic Stock Trading - Yoo, Joon Soo (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Stock trading is the process of buying and selling stocks to boost financial returns. The secret to effective stock trading is making the proper trading decisions at the right moments or developing a competent trading plan. In a lot of recent studies, machine learning (ML) approaches have been utilised to predict stock movements or prices in order to conduct stock trading. This research aims to examine the possibilities of deep reinforcement learning powered by Artificial Intelligence (AI) for enhancing the precision and efficiency of automated stock trading systems. It analyses the difficulties in performing automated stock trading and suggests a brand-new Deep Reinforcement Learning (DRL)method to overcome them. To forecast stock prices and make trading decisions, the suggested method combines a deep neural network and a Reinforcement Learning (RL) algorithm. Based on actual stock data, experiments are run to assess how well the suggested technique performs. The outcomes demonstrate that the suggested technique beats current trading strategies and can generate large increases in profitability.